2014
DOI: 10.1016/j.placenta.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the placenta of women with hypertensive disorders in pregnancy

Abstract: Introduction: Autophagy has not been studied extensively in the human placenta. This study was performed to determine whether autophagy is increased in the placentas of women with hypertensive disorders in pregnancy compared to normotensive pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 18 publications
3
55
1
1
Order By: Relevance
“…We summarized the results from studies on autophagy in the placenta from women with preeclampsia and fetal growth restriction (FGR) (Table 1) [9394959697]. Several studies have demonstrated that placenta from women with preeclampsia or FGR showed increased autophagic activity in villous trophoblasts compared with placenta from a normal pregnancy.…”
Section: Part IImentioning
confidence: 99%
See 1 more Smart Citation
“…We summarized the results from studies on autophagy in the placenta from women with preeclampsia and fetal growth restriction (FGR) (Table 1) [9394959697]. Several studies have demonstrated that placenta from women with preeclampsia or FGR showed increased autophagic activity in villous trophoblasts compared with placenta from a normal pregnancy.…”
Section: Part IImentioning
confidence: 99%
“…However, depending on the study population selected in each study, there are some conflicting points. Although some studies indicated that placentas from women with preeclampsia demonstrated increased autophagy regardless of the presence of FGR [94], other studies found that the increased autophagy in placenta was observed only in the group with preeclampsia complicated with FGR but not in the group with only preeclampsia [95]. Nonetheless, it is certain that the severity of preeclampsia or FGR is positively correlated with enhanced autophagosome formation.…”
Section: Part IImentioning
confidence: 99%
“…This is in line with previous studies in second trimester and term placenta (Oh et al 2008), suggesting induction of autophagy at all stages of pregnancy. Of note is that a previous correlation analysis suggested decreasing LC3B-II levels with advancing gestational week (Akaishi et al 2014). However, our observation of decreased LC3B-II in first-trimester placenta in response to TNF-α is in stark contrast to a previous study showing increased LC3B-II levels in TNF-α-treated Jeg-3 trophoblast cells (Oh et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…On the basis of mRNA and protein levels of autophagy markers, such as the posttranslationally modified active form of microtubule-associated protein 1 light chain 3 beta (LC3B-II), lysosome-associated membrane protein 2 (LAMP-2) and beclin-1, increased autophagy is described in placentas from pregnancies complicated by fetal growth restriction, with or without preeclampsia, but not for those with pre-eclampsia alone (Curtis et al 2013; Hung et al 2012). In contrast, other studies showed evidence for increased autophagy in placentas from hypertensive pregnancies, independent of the presence of growth restriction (Akaishi et al 2014; Oh et al 2008). Besides hypertension, maternal body mass index (BMI) and fetal sex seem to influence placental autophagy, as activation of autophagosomal formation and autophagosome–lysosome fusion have been shown in placentas from male but not female offspring of overweight and obese women.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation